ByzRev 06.2024.051: Glenn Peers, Byzantine Media Subjects.: Ithaca: Cornell University Press 2024. - Parpulov, Georgi (The Byzantine Review, 2024)
Glenn Peers, Byzantine Media Subjects. Ithaca: Cornell University Press 2024. 300 pp., 41 b&w and 38 colour ill. – ISBN 978-1-5017-7626-7